Lifshitz solutions in supergravity and string theory - Gregory, Ruth; Parameswaran, Susha L.; Tasinato, Gianmassimo; Zavala, Ivonne (Journal of high energy physics, 2010)
We derive Lifshitz configurations in string theory for general dynamical exponents z ≥ 1. We begin by obtaining simple Li × Ω solutions to supergravities in diverse dimensions, with Ω a compact constant curvature manifold. Then we uplift the solutions to ten dimensions, providing configurations that correspond to warped compactifications in Type II string theory.